2014
DOI: 10.1590/0303-7657000072212
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes de trabalho com óbito: o jornal impresso como fonte de informação

Abstract: ResumoObjetivo: descrever os acidentes de trabalho com óbito noticiados nos três principais jornais impressos do Estado da Bahia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
1
1
0
3
Order By: Relevance
“…This study found statistically significant relationships between certain sociodemographic variables and the possibility of death in the event of an occupational injury. Some of these associations have been reported previously by other studies of the working population, such as: being male [ 4 , 25 , 36 46 ], age [ 4 , 36 – 40 , 47 51 ], length of time employed [ 12 , 36 , 44 , 50 ] and occupation [ 19 , 20 , 50 , 52 ]. In addition, a greater possibility of a fatal outcome was found among workers in the construction, mining and industrial manufacturing sectors.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This study found statistically significant relationships between certain sociodemographic variables and the possibility of death in the event of an occupational injury. Some of these associations have been reported previously by other studies of the working population, such as: being male [ 4 , 25 , 36 46 ], age [ 4 , 36 – 40 , 47 51 ], length of time employed [ 12 , 36 , 44 , 50 ] and occupation [ 19 , 20 , 50 , 52 ]. In addition, a greater possibility of a fatal outcome was found among workers in the construction, mining and industrial manufacturing sectors.…”
Section: Discussionsupporting
confidence: 55%
“…This finding is similar to that of a Spanish study which reported that the organization of the work and prevention measures were accountable for the largest proportion of the factors involved in fatal injuries among the working population in Spain [ 62 ]. Other studies have found the environment and workplace conditions to be relevant factors for causing fatal and non-fatal occupational injuries [ 46 , 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associado a isto, percebeu-se que no período entre 2013 a 2018, cerca de 62% dos óbitos tiveram como causas acidentes de transporte e 41,4% ocorreram em vias públicas (SILVA, 2017). Segundo Feitosa et al, (2014), isso pode ser explicado devido ao maior número de vítimas vir do setor de transporte, visto que, acidentes de transito estão entre as principais causas de mortes no Brasil e no mundo (BITTAR et al, 2020). Ademais, é importante salientar o expressivo número de mortes por violência intencional, evidenciando o impacto emocional sobre a rotina desses trabalhadores (FEITOSA et al, 2014).…”
Section: Discussionunclassified
“…Segundo Feitosa et al, (2014), isso pode ser explicado devido ao maior número de vítimas vir do setor de transporte, visto que, acidentes de transito estão entre as principais causas de mortes no Brasil e no mundo (BITTAR et al, 2020). Ademais, é importante salientar o expressivo número de mortes por violência intencional, evidenciando o impacto emocional sobre a rotina desses trabalhadores (FEITOSA et al, 2014).…”
Section: Discussionunclassified